GABAergic transmission and enhanced modulation by opioids and endocannabinoids in adult rat rostral ventromedial medulla. (25th November 2014) - Li, Ming‐Hua; Suchland, Katherine L.; Ingram, Susan L.
Abstract : Key points: Electrical stimulation of the rostral ventromedial medulla (RVM) facilitates pain behaviours in neonates but inhibits these behaviours in adults. The cellular mechanisms underlying these changes in RVM modulation of pain behaviours are not known. We optimized whole‐cell patch‐clamp recordings for RVM neurons in animals older than postnatal day 30 and compared the results to postnatal day 10–21 animals. Our results demonstrate that the γ‐aminobutyric acid (GABA) release is lower and opioid effects are more evident in adult rats compared to early postnatal rats. A cannabinoid receptor antagonist significantly increased GABA release in mature but not in immature RVM neurons suggesting the presence of local endocannabinoid tone in mature RVM. Abstract: Neurons in the rostral ventromedial medulla (RVM) play critical and complex roles in pain modulation. Recent studies have shown that electrical stimulation of the RVM produces pain facilitation in young animals (postnatal (PN) day < 21) but predominantly inhibits pain behaviours in adults. The cellular mechanisms underlying these changes in RVM modulation of pain behaviours are not known. This is in part because whole‐cell patch‐clamp studies in RVM to date have been in young (PN day < 18) animals because the organization and abundance of myelinated fibres in this region make the RVM a challenging area for whole‐cell patch‐clamp recording in adults. Several neurotransmitter systems, including GABAergic neurotransmission, undergo developmental changes that mature by PN day 21. Thus, we focused on optimizing whole‐cell patch‐clamp recordings for RVM neurons in animals older than PN day 30 and compared the results to animals at PN day 10–21. Our results demonstrate that the probability of GABA release is lower and that opioid and endocannabinoid effects are more evident in adult rats (mature) compared to early postnatal (immature) rats. Differences in these properties of RVM neurons may contribute to the developmental changes in descending control of pain from the RVM to the spinal cord.